Factors associated with utilization of modern postpartum family planing methods during the extended postpartum period among mothers who gave birth in the last 12 months at Injibara town, Northwest, Ethiopia: a cross-sectional study - Getachew Andualem; Almaz Aklilu; Getahun Belay; Wondu Feyisa; Fentahun Alemnew (BMC, 2022)
Abstract Background The extended postpartum period is the first twelve months following childbirth and is an important entry point for family planning service providers to reduce unintended and too closely spaced pregnancies. A modern postpartum family planning service is one of the recommended public health interventions for reducing maternal and child morbidity and mortalities in sitting where maternal mortality is high, like in Ethiopia. Objective This study was aimed to assess factors associated with the utilization of modern family planning methods during the extended postpartum period among mothers who gave birth in the last 12 months at Injibara town, Northwest, Ethiopia. Methods A community-based cross-sectional study design was employed from March 1-15/2019 at Injibara town among 402 mothers. The data was collected by a simple random sampling technique and analyzed using the SPSS 23.0 version. Logistic regression analyses were employed to estimate the crude and adjusted odds ratio with a confidence interval of 95% and a P-value of < 0.05 in multivariable analysis considered statistically significant. Frequency tables and descriptive summaries were used to describe the study variables. Results The total sample size of this study was 402 and among them, 400 postpartum mothers participated in the study with a response rate of 99.5%. The utilization of modern family planning methods during the extended postpartum period among postpartum mothers was 58.5% [95% CI: 53.5- 63%]. Of these, 38.9% and 32.9% of the mothers were using injectables and implants respectively. Secondary and above educational level, having ≥ 3 antenatal care visits, resumption of menstruation, discussing with the partner on utilization of family planning method, being counseled on family planning method utilization during antenatal care visits and immediately after delivery, linkage of the mothers to a family planning unit during child immunization, and having good knowledge of family planning methods were associated with utilization of modern family planning methods during the extended postpartum period. Conclusion The utilization of modern family planning methods during the extended postpartum period among postpartum women was low compared to the world health organization recommendation. Socio-demographic, health care service uptakes, and reproductive characteristics were associated with the utilization of modern family planning methods during the extended postpartum period. We suggest emphasizing the education and counseling of women on the utilization of family planning during maternal and child health care service utilization. Mothers should be encouraged to start using modern family planning methods before the resumption of menses.